An experimental investigation of an energy regeneration suspension - Tho, Nguyen Huu; Danh, Le Thanh (National Research and Innovation Agency, 2024)
Energy absorbed from road bumps in traditional suspensions is dissipated as heat. An energy regeneration suspension (ERS) has the capability to capture and store this energy in batteries. It has the potential to be used in several categories of vehicles, encompassing cars, trucks, buses, and even trains. ERS technology shows significant promise in enhancing the fuel efficiency and environmental sustainability of vehicles. In this paper, the design of an ERS that converts kinetic energy into electrical energy is presented. The primary objective is to identify key design parameters that result in high magnetic intensity levels in the air gap of the ERS model. Optimizing these parameters is essential to maximize the advantages of ERS while minimizing any drawbacks. The study investigates the impact of different magnetic permeability materials in the ERS model using ANSYS software. A test rig is established based on the analysis results to assess the energy regeneration efficiency of the ERS model under various excitations. Experimental results demonstrate that ERS models with higher permeability inner sleeves exhibit superior energy regeneration efficiency.